Container baby syndrome – has infant equipment overuse an impact on motor skill development? - Michalska, Agata; Połatyńska, Katarzyna; Gładyś-Jakubczyk, Aleksandra; Kędzierski, Sebastian; Pogorzelska, Justyna (Pediatria Polska - Polish Journal of Paediatrics, 2023)
The popularity of the use of accessories supporting baby caring such as rockers, car seats, baby carriers, and walkers is defined as container culture or container lifestyle. There is a tendency to use such items incorrectly, often leaving the infant without parental supervision. Reduction of a child’s spontaneous motor activity, prolonged stay in a forced supination position, premature sitting, or premature standing cause disturbances in motor, cognitive, social, and emotional development. The aim of the study is to present the problem of container baby syndrome. We would like to present recommendations that can be used during the parents’ education, to raise their awareness of proper conduct and stimulation of their child’s development.